The development of PISA reading competence in secondary education - Jovanović Vitomir; Baucal Aleksandar (Psihološka Istraživanja, 2016)
The aim of the paper is to provide a contribution to answering the question about the most important predictors of progress in reading competence achieved by students after two years of secondary education, as well as whether the set of predictors of progress is different from the set of predictors of achievement in reading literacy test and school achievement measured via school grades. The students from the sample for the PISA 2009 study conducted in Serbia were tested again after two years by the PISA reading literacy test, quasi longitudinally, measuring achievement correlates at another time point. The realised sample included 20 secondary schools and 446 students. We selected fourteen predictors that, according to the studies so far, proved to have highest correlations with school achievement. The results have shown that the predictors explain only 13% of variance of the progress in reading literacy test (R=.36; R2=.13; F =12.97; p<.05) although they explain 49% of variance of achievement at it (R=.70; R2 197,18 =.49; F257,18 =12.97; p<.001). This opens up the issue of the importance of early learning for progress in reading competence. In both the first and the second analysis, the strongest predictor was the autonomous form of extrinsic motivation which, according to the self-determination theory, speaks about the importance of learning for future life and career. A somewhat different set of used predictors predicted school achievement measured via school grades. Using metacognitive strategies is not an important predictor of school achievement while it is the predictor of achievement in the reading literacy test. Together with the findings pointing towards the lower than expected correlation between achievement in reading literacy and school achievement (r=.39; p<0.001) and generally low progress of Serbia at this test compared to the estimated progress of the OECD countries, these results give grounds for the conclusion that our educational system does not promote sufficiently the development of reading competence.